Research on the multi-channel operation of MAC protocol in wireless sensor networks. Issue 2 (4th March 2022) - Chen, Yang; Yuan, Shuping; Gu, Fenfei
Abstract : This paper briefly introduced Wireless Sensor Network (WSN) and the competitive Medium Access Control (MAC) protocol for assisting the multi-channel operation in WSN. Then, the avoidance operation of the traditional competitive MAC protocol was improved. The WSN that adopted two MAC protocols was simulated in the MATLAB software, and the performance of WSN under different node number was tested. The results showed that the WSN that adopted the traditional MAC protocol had decreased throughput and channel utilization and increased average time delay with the increase of node number in the WSN; the WSN that adopted the improved MAC protocol had decreased throughput and relatively stable average time delay and channel utilization with the increase of node number in the WSN; under the same number of nodes, the WSN that adopted the improved MAC protocol had higher throughput and channel utilization and lower average time delay. GRAPHICAL ABSTRACT: UF0001